DIGITAL LITERACY EDUCATION FOR HIGH SCHOOL TEACHERS IN SATU GEDANGAN TO INCREASE INSIGHT AND MITIGATE HOAXES - Alit Widana; Tutut Wurijanto; Teguh Sutanto; Slamet (Ann Publisher, 2026)
Abstract Background. The development of internet technology and artificial intelligence (AI) technology has increased rapidly. By 2025 alone, hundreds of artificial intelligence (AI)-based technologies are expected to help complete human work faster and more efficiently. Based on statistics reported in the mass media, the amount of content uploaded increased by up to 200%. The problem is that the content may contain false information, also known as hoaxes. Aims. The purpose of this service is to enhance the insight of SMA Negeri Satu Gedangan teachers in digesting content in a more structured manner and avoid falling victim to hoax content. Methods. The method employed was a digital literacy workshop, accompanied by questionnaires administered at the beginning and end of the workshop. Result. The result of the digital literacy workshop was an increase in the ability of SMA Negeri Satu Gedangan teachers to digest and understand content on social media from an average of 60% to 100%. Implementation. The expected impact is that educators with good digital literacy skills can educate students more effectively and prevent them from becoming victims of hoaxes.